Concomitant Transverse Myelitis and Acute Axonal Sensory-Motor Neuropathy in an Elderly Patient - L. M. Oliveira; R. G. Cury; L. H. Castro; R. Nitrini (Case Reports in Immunology)
Diagnosing concomitant transverse myelitis (TM) and Guillain-Barré syndrome (GBS) can be challenging. We report a case of an elderly patient presenting with acute sensory and motor disturbances in the four limbs, associated with urinary retention, ophthalmoparesis, facial weakness, and dysarthria. Electrodiagnostic studies were consistent with acute motor sensory axonal neuropathy (AMSAN), and imaging showed a longitudinally extensive tumefactive contrast-enhancing hyperintense spinal cord lesion extending from T6 to the cone. Concomitant AMSAN and TM have not been previously reported in the elderly. Comorbid TM and other GBS variants have been previously reported. Intravenous methylprednisolone, plasma exchange, cyclophosphamide, or combination therapies are usually used, although there are no randomized controlled studies regarding treatment choices.